1999
DOI: 10.1172/jci7209
|View full text |Cite
|
Sign up to set email alerts
|

DNA immunization to prevent autoimmune diabetes

Abstract: Mice expressing lymphocytic choriomeningitis virus nucleoprotein (LCMV-NP) as a transgene in their β cells develop insulin-dependent diabetes mellitus (IDDM) only after LCMV infection. Inoculation of plasmid DNA encoding the insulin B chain reduced the incidence of IDDM by 50% in this model. The insulin B-chain DNA vaccination was effective through induction of regulatory CD4 lymphocytes that react with the insulin B chain, secrete IL-4, and locally reduce activity of LCMV-NP-autoreactive cytotoxic T lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 26 publications
3
93
1
Order By: Relevance
“…Our results are also consistent with a growing notion that the efficacy at which Th2 cell differentiation can be induced in an Ag-specific manner is dependent on the frequency of established Th1 effector cells and uncommitted T cell precursors. For example, Coon et al (42) showed that immunization with pDNA-encoding porcine insulin B chain elicited Th2 cell reactivity and prevented diabetes induced by lymphocytic choriomeningitis virus (LCMV) infection in BALB/c mice expressing LCMV nucleoprotein in ␤ cells (42). In contrast, when established T cell effectors already existed, i.m.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also consistent with a growing notion that the efficacy at which Th2 cell differentiation can be induced in an Ag-specific manner is dependent on the frequency of established Th1 effector cells and uncommitted T cell precursors. For example, Coon et al (42) showed that immunization with pDNA-encoding porcine insulin B chain elicited Th2 cell reactivity and prevented diabetes induced by lymphocytic choriomeningitis virus (LCMV) infection in BALB/c mice expressing LCMV nucleoprotein in ␤ cells (42). In contrast, when established T cell effectors already existed, i.m.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported protection against autoimmune diabetes by DNA vaccination against isletcell antigens (insulin, GAD65 or other) in NOD mice or other diabetes models (Table 3). [50][51][52][53][54][55][56][57][58][59][60][61] In the vast majority of cases, DNA was delivered i.m. without electroporation.…”
Section: Dna Vaccination Against T1dmentioning
confidence: 99%
“…Antigen-specific prevention of T1DM can be achieved in several ways in animal models, (i) with DNA vaccines [5][6][7], (ii) peptide derived from islet antigens [8,9], or (iii) full-length islet proteins [10,11] (Table 1). The use of DNA vaccination to prevent T1DM was pioneered by our group, and corroborated and extended by other laboratories.…”
Section: Antigen-specific Prevention Of Type 1 Diabetesmentioning
confidence: 99%